Peningkatan Kapasitas Petani Muhammadiyah dalam Seleksi Benih pada Budidaya Padi System of Rice Intensification - Gatot Supangkat Samidjo; Agung Astuti; Mulyono Mulyono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Rice production in Muhammadiyah Godean farmers is still low at around 5 tons/ha. One of the problems is the use of seeds that are too old, the growth power is low, so it requires large amounts of seeds. The solution is to be given the understanding and skills in seed selection using a salt solution so that the seeds are pithy, have high growth power, and are efficient. The purpose of empowering Muhammadiyah Godean farmers is to increase their knowledge and skills regarding seed selection using the salt solution in System of Rice Intensification (SRI) rice cultivation. The Direct Learning method is applied in program implementation. The activities carried out include counseling, training, and assistance during seed selection, testing for growth power, and seed quality. The evaluation results using pre and post-tests showed that 53% of farmers had already known the salt selection method but had not been able to do it (53%) and were very eager to learn (80%). After counseling, there was an increase in understanding of 47%. The program results stated that all farmers understood (100%) and could select seeds using the salt solution method, and 73% found it easy. SRI rice cultivation with the initial stages of seed selection with the salt solution selection method can be obtained seed efficiency of about 60-75%.